Mathematical analysis of ROC-TOPSIS method for prioritizing road repair decisions - Sur, Widiya Astuti Alam; Machfiroh, Ines Saraswati (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
Determining the priority of road damage in road construction typically relies on assessments based on the Pavement Condition Index (PCI) method. However, the PCI classification does not provide specific criteria to distinguish between road sections within the same classification, complicating the identification of sections in worse condition. To address this issue, mathematical analysis can employ multi-criteria decision-making (MCDM) methods to prioritize road sections for repair. One effective approach is the integration of the Rank Order Centroid (ROC) and Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) methods. The analysis results indicate that the road sections prioritized for repair were located at Location III: Alternative 70, Alternative 80, and Alternative 42. Based on the Pearson correlation coefficient between the ranking orders of the pavement assessment using PCI and ROC-TOPSIS, there is a 65% similarity. Consequently, ROC-TOPSIS can serve as an alternative method for determining priority repairs, as it aligns with the results of the road pavement assessment.